Impact of COVID‐19 Pandemic on Liver Transplantation and Alcohol‐Associated Liver Disease in the USA. Issue 6 (28th September 2021) - Cholankeril, George; Goli, Karthik; Rana, Abbas; Hernaez, Ruben; Podboy, Alexander; Jalal, Prasun; Da, Ben L.; Satapathy, Sanjaya K.; Kim, Donghee; Ahmed, Aijaz; Goss, John; Kanwal, Fasiha
Abstract : Background and Aims: The surge in unhealthy alcohol use during the COVID‐19 pandemic may have detrimental effects on the rising burden of alcohol‐associated liver disease (ALD) on liver transplantation (LT) in the USA. We evaluated the effect of the pandemic on temporal trends for LT including ALD. Approach and Results: Using data from United Network for Organ Sharing, we analyzed wait‐list outcomes in the USA through March 1, 2021. In a short‐period analysis, patients listed or transplanted between June 1, 2019, and February 29, 2020, were defined as the "pre‐COVID" era, and after April 1, 2020, were defined as the "COVID" era. Interrupted time‐series analyses using monthly count data from 2016‐2020 were constructed to evaluate the rate change for listing and LT before and during the COVID‐19 pandemic. Rates for listings ( P = 0.19) and LT ( P = 0.14) were unchanged during the pandemic despite a significant reduction in the monthly listing rates for HCV (−21.69%, P < 0.001) and NASH (−13.18%; P < 0.001). There was a significant increase in ALD listing (+7.26%; P < 0.001) and LT (10.67%; P < 0.001) during the pandemic. In the COVID era, ALD (40.1%) accounted for more listings than those due to HCV (12.4%) and NASH (23.4%) combined. The greatest increase in ALD occurred in young adults (+33%) and patients with severe alcohol‐associated hepatitis (+50%). Patients with ALD presented with a higher acuity of illness, with 30.8% of listings and 44.8% of LT having a Model for End‐Stage Liver Disease–Sodium score ≥30. Conclusions: Since the start of COVID‐19 pandemic, ALD has become the most common indication for listing and the fastest increasing cause for LT. Collective efforts are urgently needed to stem the rising tide of ALD on health care resources.